Diacylglycerol kinase alpha regulates post-hepatectomy liver regeneration - Hiroki Nakamoto; Shunsuke Shichi; Chisato Shirakawa; Takuto Suzuki; Hidemitsu Kitamura; Akinobu Taketomi (Scientific Reports)
Abstract Diacylglycerol kinases (DGKs) phosphorylate diacylglycerol to generate phosphatidic acid, which plays important roles in intracellular signal transduction. DGKα is reportedly associated with progression of tumors, including hepatocellular carcinomas, but its relationship with liver regeneration has not been examined. The purpose of this research is to elucidate the role of DGKα in liver regeneration. Here, we provide a detailed examination of C57BL/6 wild-type and DGKα knockout (KO) mice subjected to 70% partial hepatectomy (70% PH) modeling, including survival rates, hematological marker and gene expression levels, and histological analyses of factors related to liver regeneration. Following 70% PH, DGKα KO mice produce higher levels of hepatobiliary enzymes and have a higher incidence of jaundice compared with wild-type mice, with a death rate of ~ 40%. Furthermore, they exhibit impaired glycogen and lipid consumption, low liver energy charge, and hepatocyte hypertrophy disorder, accompanied by significantly reduced liver expression of proliferating cell nuclear antigen and cyclin D. We conclude that DGKα is a key molecule in the post-PH liver regeneration process and may have potential as a therapeutic target for the acceleration of liver regeneration.